Uncovering host-microbe dynamics in benthic invertebrates of the little-known coastal hydrothermal vents in the Gulf of Patti (Sicily) - Francesco Fabiano; Erika Arcadi; Michela D'Alessandro; Valentina Esposito; Carmen Rizzo; Teresa Romeo (Ocean & Coastal Management, 2026)

Big sharks in the dark: High densities of the bluntnose sixgill shark Hexanchus griseus in the Gulf of Naples - Simona Noè; Francesco Stenico; Frine Cardone; Antonio Terlizzi; Simonepietro Canese; Teresa Romeo; Chiara Bonaviri; Andrea Aiello; Trevor J. Willis (Ecology, 2026)

Expanding knowledge of deep-sea coronatae medusae (Cnidaria, Scyphozoa) in the Mediterranean through ROV-based in situ documentation - Frine Cardone; Antonio Giova; Simonepietro Canese; Valentina Costa; Martina Genovese; Teresa Romeo; Eva Salvati; Francesco Stenico; Silvestro Greco (Marine Biology, 2026)

Low-Cost Technologies for Marine Habitat Monitoring: A Case Study on Seagrass Meadows - Valentina Costa; Teresa Romeo (Journal of Marine Science and Engineering, 2026)
Seagrass meadows are essential coastal ecosystems that provide key ecological services, including carbon sequestration, sediment stabilization, and shoreline protection. Increasing threats from natural and anthropogenic stressors highlight the need for efficient, reproducible, and non-invasive monitoring solutions. This study evaluates the performance of low-cost commercial drones for seagrass assessment in shallow coastal waters, with an emphasis on freely accessible mission-planning and photogrammetric workflows. Field surveys were conducted along the Calabrian coast (southern Italy), where automated flight paths were generated using the software WaypointMap, and high-resolution orthophotos were generated using the WebODM software and subsequently analyzed in QGIS for seagrass patch detection, mapping, and surface estimation. The methodological pipeline is described in detail to facilitate full reproducibility. Compared with traditional diver-based methods, this workflow offers faster data collection, broader spatial coverage, and minimal environmental disturbance. Although some limitations remain, the results demonstrate that combining low-cost drones with open-source tools provides a practical and scalable solution for routine monitoring. This approach has strong potential for integration into routine coastal habitat assessment, supports early impact detection, and contributes to evidence-based conservation and management strategies.

No place to hide: Assessing habitat shifts of Benthocometes robustus from Cold-Water corals to marine litter in the Mediterranean Sea - Ludovica De Vincenzis; Pietro Battaglia; Valeria Palummo; Giacomo Milisenda; Simonepietro Canese; Frine Cardone; Daniela Pica; Eva Salvati; Francesco Stenico; Pierpaolo Consoli; Valentina Costa; Antonio Giova; et al. (Marine Environmental Research, 2026)

Metal(loid)s in mesopelagic fishes from the Mediterranean food web - Mauro Cavallaro; Teresa Romeo; Vittorio Lo Presti; Alessandro Giuffrida; Filippo Giarratana; Graziella Ziino; Luca Nalbone; Antonino Nazareno Virga; Nicola Cicero; Giuseppa Di Bella; Giovanni Ammendolia; Monia Renzi; et al. (Marine Pollution Bulletin, 2026)

Temporal changes in the diet composition of swordfish, Xiphias gladius (Linnaeus, 1758), in a Mediterranean foraging and reproductive ground - Pietro Battaglia; Danilo Malara; Cristina Pedà; Davide Ciraolo; Teresa Romeo (Marine Environmental Research, 2026)

Microplastic occurrence in the digestive system and health status assessment in a commercially important cephalopod species, Sepia officinalis from the Gulf of Patti (southern Tyrrhenian Sea) - Cristina Pedà; Danilo Malara; Francesco Longo; Federica Laface; Pietro Battaglia; Claudio Berti; Pierpaolo Consoli; Giovanna Ponte; Paul Andrews; Silvestro Greco; Teresa Romeo (Marine Pollution Bulletin, 2025)

New records of rarely reported species in the Mediterranean Sea (March 2025) - JOSÉ CARLOS BÁEZ; OKAN AKYOL; ERNESTO AZZURRO; PIETRO BATTAGLIA; ANGEL BELMONTE-GALLEGOS; GEORGIOS CHRISTIDIS; FABIO CROCETTA; CEM DALYAN; YUNUS GÖNÜL; FABIO GRATI; SILVESTRO GRECO; CHRYSOULA GUBILI; et al. (Mediterranean Marine Science, 2025)
This collective study presents information on fifteen (15) species recorded across five countries (Greece, Italy, Slovenia, Spain, and Türkiye) and four (4) ecoregions, ranging from the Alboran Sea to the Aegean Sea. The recorded species belong to three phyla: Mollusca (3 species), Arthropoda (3 species), and Chordata (9 species). Among mollusks, Martadoris mediterranea is reported for the first time in the Aegean Sea at two different locations, while Opisthoteuthis calypso and Octopoteuthis sicula are newly recorded in the western Mediterranean. Regarding arthropods, Ocypode cursor is reported from the Tyrrhenian coast of Sicily, Pachygrapsus transversus is recorded for the first time in the Tyrrhenian Sea, and Cancer pagurus in the Sea of Marmara. Among chordates, Lobotes surinamensis and Zu cristatus are newly recorded in the Alboran Sea, while Callionymus fasciatus and Symphodus doderleini are reported from Slovenian coastal waters. Tripterygion delaisi and Gymnothorax unicolor are documented for the first time in the waters of the Sea of Marmara and Crete, respectively. Additionally, new records of rarely reported fish species include Arctozenus risso, Chromogobius zebratus, and Epinephelus aeneus in Turkish, Spanish, and Italian waters, respectively.

Biodiversity at risk in the SPAMI Pelagos Sanctuary: The impact of marine litter on biota - Maria Cristina Fossi; Matteo Baini; Matteo Galli; Paola Tepsich; Francesca Grossi; Margherita Concato; Dario Giani; Massimiliano Rosso; Anna Borroni; Teresa Romeo; Cristina Panti (Science of The Total Environment, 2025)

First evidence of microplastic ingestion by the European grayling, Thymallus thymallus, in sub-Arctic regions: Insights on plastic pollution and preliminary risk assessment in the Teno River (Finland) - Cristina Pedà; Carmen Rizzo; Federica Laface; Stefania Giannarelli; Pietro Battaglia; Teresa Romeo; Angelina Lo Giudice (Science of The Total Environment, 2024)

Testing best practices in small scale fisheries management: Evidence from a collaborative intervention in two marine protected areas of the central Mediterranean Sea - Serena Zampardi; Claudia Scianna; Antonio Calò; Katie Hogg; Marco Ranù; Giorgio Aglieri; Emanuela Di Meglio; Maria Cristina Mangano; Giulia Prato; Teresa Romeo; Francesco Colloca; Giacomo Milisenda; et al. (Ocean & Coastal Management, 2024)

Synthetic polymers: A global threat to aquatic benthic environments - Pierpaolo Consoli; Valentina Costa; Valentina Sciutteri; Danilo Malara; Cristina Pedà; Fabio Figurella; Ian Campbell; Emily Deery; Teresa Romeo; Franco Andaloro (Journal of Hazardous Materials, 2024)

Structural diversity of Leiopathes glaberrima populations in the strait of Sicily: from pristine to declining forests - Antonio Giova; Simonepietro Canese; Benedetta Zoe Donelli; Teresa Romeo; Silvestro Greco (Frontiers in Marine Science, 2024)
Introduction The black coral Leiopathes glaberrima is a key component of deep-sea animal forests of the Western Mediterranean and North-Atlantic hard bottoms. Due to its ecological role, biological characteristics and sensitivity to fishing activities, it has been included in the Annex II of the Barcelona Convention, listed as an endangered species in IUCN Red Lists, and recognized as an indicator of Vulnerable Marine Ecosystems by the FAO. Methods During a survey conducted in the Strait of Sicily, 140 ROV transects were carried out allowing the characterization of environmental preferences, associated fauna and population structure of L. glaberrima in the study area. Results and discussion 1020 colonies were distributed between 165 and 672 meters and arranged in 17 patches and isolated colonies. The average height was determined to be 40.9 ± 1.0 cm, with the range spanning from a minimum of 5 cm up to nearby 200 cm. Pristine colonies accounted for 62.9%, mainly constituted by small-sized individuals densely aggregated (up to 14.5/m2 in a single frame) in the eastern part of the area. 24.5% of the specimens were dead and localized in the western margin where we reported a rare case of mass mortality in the deep-sea environment and the first ever described for black corals, opening new scenarios regarding the possibility that these events can occur in environments previously considered safe from danger. The triggering causes of these events in inaccessible environments are actually only hypothesized, but it is not to be excluded that, sooner or later, a similar effect could potentially result from anthropogenic climate changes.

Satellite tagging insights into the seasonal movements and behavior of Mediterranean spearfish (Tetrapturus belone, Istiophoridae) - Danilo Malara; Pietro Battaglia; Martin C. Arostegui; Jonathan J. Dale; Barbara A. Block; Camrin D. Braun; Massimo Brogna; Silvestro Greco; Teresa Romeo (Frontiers in Marine Science, 2024)
The Mediterranean spearfish ( Tetrapturus belone ) is a highly migratory predator, also exploited by commercial and recreational fisheries although its catches are poorly reported. The fishing pressure on this species is currently unknown because catch and landing data are fragmentary. Furthermore, more ecological information (e.g. migratory movements) is needed to establish eventual management measures, and ICCAT has not examined the population status yet. Understanding species migratory movements is crucial for addressing conservation challenges and supporting management decisions. In this study we investigated the migratory movements, seasonal patterns, vertical behavior, and thermal preference of T. belone , with the aim to improve information on its ecology and behavior. Overall, six individuals were tagged in the Strait of Messina and Tyrrhenian Sea with pop-up satellite tags and their movements were mainly restricted to the central Mediterranean. Utilization distributions derived from geolocation revealed an overall and seasonal importance of the Tyrrhenian Sea and Strait of Sicily, as well as variability in winter habitat use. While the fish exhibited similar depth preference, spending the majority of time at depths ≤ 10 m, we observed that the Mediterranean spearfish is also able to perform sporadic deep dives below 200 m. Vertical movement showed a bimodal pattern common in other billfish species, characterized by occupation of shallower, warmer waters during the night and deeper, cooler waters during the day. This research increases knowledge on the migration ecology and habitat preference of T. belone which is important for management of this understudied species.

PCB bioremediation potential of thermophilic strains from shallow hydrothermal vent (Vulcano Island) - Rosario Calogero; Erika Arcadi; Francesco Fabiano; Carmen Rizzo; Teresa Romeo; Silvestro Greco (Journal of Water Process Engineering, 2024)

Improving the knowledge base of Vulnerable Marine Ecosystems’ distribution in the Amendolara Bank (Ionian Sea) - VALERIA PALUMMO; GIACOMO MILISENDA; DANIELA PICA; SIMONEPIETRO CANESE; EVA SALVATI; NUNZIACARLA SPANÒ; TERESA ROMEO; SILVESTRO GRECO (Mediterranean Marine Science, 2024)
The Amendolara Bank was recently designated as a Site of Community Importance; however, information on its ecosystems remains limited, with a particular dearth of knowledge regarding the deeper zone (>100 m). Previous studies have discovered the existence of Vulnerable Marine Ecosystems (VMEs) within the bank, underscoring the necessity for more comprehensive data and its significance in terms of conservation in the Ionian Sea. This study aims to investigate various aspects of the bank using Remotely Operated Vehicles (ROVs) to shed light on the possible presence of VME indicator species, their relationship with environmental variables, their connection with the observed fish, and to assess anthropogenic impact via the identification of fishing gear within the study area. This present research provides new information on the biodiversity of the Amendolara Bank, revealing the presence of four VME indicator species including the first sightings of black coral Antipathella subpinnata and the precious red coral Corallium rubrum. Moreover, it provides evidence on the interaction between fish fauna and VME indicator species as well as signs of anthropogenic impact from abandoned, lost, or otherwise discarded fishing gear (ALDFG). These findings highlight the urgent need for additional research to improve the knowledge base on the biodiversity of this unique spot in the Ionian Sea which would in turn ensure the development and implementation of more effective conservation and management measures.

Deciphering the evolvement of microbial communities from hydrothermal vent sediments in a global change perspective - Carmen Rizzo; Erika Arcadi; Rosario Calogero; Alessandro Ciro Rappazzo; Gabriella Caruso; Giovanna Maimone; Angelina Lo Giudice; Teresa Romeo; Franco Andaloro (Environmental Research, 2024)

Effect of environmental and anthropogenic factors on the distribution and co-occurrence of cold-water corals - Valeria Palummo; Giacomo Milisenda; Simonepietro Canese; Eva Salvati; Daniela Pica; Augusto Passarelli; Nunziacarla Spanò; Teresa Romeo; Silvestro Greco (Frontiers in Marine Science, 2023)
Cold-water corals (CWCs) are bioengineering species that can increase habitat heterogeneity and improve the deep sea’s biological diversity and ecosystem functioning. Knowledge of their distribution provides a critical baseline for assessing the effect of natural and anthropogenic impacts on these important deep-sea habitats. The aims of this study are: i) provide new data on the spatial distribution of six CWCs species in the Strait of Sicily, ii) describe the principal environmental and anthropogenic variables that play a role in shaping their distribution, iii) identify hotspots in which individuals belonging to the various species co-occur. Presence-only data of six CWCs species, ten environmental variables (depth, slope, rugosity, aspect, flowdir, temperature, salinity, north bottom current, east bottom current, chlorophyll-a), and one variable relating to bottom trawling effort (Automatic Information System – AIS) were used to predict the suitable habitats. We used Maximum Entropy modelling (MaxEnt) approach and used the AUC (area under the receiver operating characteristic curve) and TSS (true skill statistics) to evaluate the model performance. The results showed excellent AUC, TSS and AUC’s standard deviation mean values for all six species. The validation show high predictive performance. MaxEnt identified slope, depth, and rugosity as the most important predictors, showing the highest percentage contribution for all six species considered. Throughout the study area, highlyinterspecific persistent density hotspot of CWCs co-occurrence were discovered, with a total extension of 4.05 km 2 where all species co-occur. Although studies on the effect of environmental and anthropogenic factors that impact the distribution of these species of conservation interest remain scarce, the results of this study offer useful guidance for decision-makers to develop necessary conservation measures.

Oceanographic and anthropogenic variables driving marine litter distribution in Mediterranean protected areas: Extensive field data supported by forecasting modelling - Matteo Galli; Matteo Baini; Cristina Panti; Dario Giani; Ilaria Caliani; Tommaso Campani; Massimiliano Rosso; Paola Tepsich; Vanessa Levati; Federica Laface; Teresa Romeo; Gianfranco Scotti; et al. (Science of The Total Environment, 2023)

A glimpse into the future: A suitable methodological approach for the detection and identification of micro-bioplastics in biota - Federica Laface; Cristina Pedà; Chiara Giommi; Serena Scozzafava; Carmen Rizzo; Danilo Malara; Silvestro Greco; Teresa Romeo (Science of The Total Environment, 2023)

Local businesses' consumption and perception of Single-Use Plastics: A preliminary assessment for conservation and mitigation plans in the Egadi Islands Marine Protected Area - Martina Genovese; Maria Cristina Mangano; Federica Papa; Teresa Romeo; Silvestro Greco (Marine Pollution Bulletin, 2023)

Reducing marine litter pollution from anchored fish aggregating devices: Sicilian good practices and the legislative paradox - Francesca De Domenico; Cristina Pedà; Claudio Berti; Pierpaolo Consoli; Francesco Longo; Silvestro Greco; Teresa Romeo (Marine Policy, 2023)

Integrated approach for marine litter pollution assessment in the southern Tyrrhenian Sea: Information from bottom-trawl fishing and plastic ingestion in deep-sea fish - Valentina Sciutteri; Cristina Pedà; Francesco Longo; Rosario Calogero; Giuseppe Cangemi; Luca Pagano; Pietro Battaglia; Matteo Nannini; Teresa Romeo; Pierpaolo Consoli (Marine Pollution Bulletin, 2023)

Isolation and Identification of Luminescent Bacteria in Deep Sea Marine Organisms from Sicilian Waters (Mediterranean Sea) - Rosario Calogero; Carmen Rizzo; Erika Arcadi; Maria Giulia Stipa; Pierpaolo Consoli; Teresa Romeo; Pietro Battaglia (Journal of Marine Science and Engineering, 2022)
Luminescent bacteria are a fascinating component of marine microbial communities, often related to the light emissions in deep sea marine organisms. They are mainly affiliated with specific phylogenetic groups, such as Photobacterium, Vibrio, and Photorhabdus, and are sometimes involved in symbiotic relationships. However, the luminescence of some marine organisms remains a poorly understood process, and it is not always certain whether their luminescence is attributable to associated luminescent bacteria. In this study, for the first time, luminescent bacteria were isolated from two deep sea organisms, namely, the cephalopod Neorossia caroli and the teleost Chlorophthalmus agassizi. The isolation was carried out on glycerol-supplemented medium, and the search for the luxAB gene was performed on all isolates as a complementary tool to the culture-dependent techniques to detect bioluminescence by molecular approach. The optimum of salinity, temperature, and pH was evaluated by physiological tests for all isolates. The production of extracellular polymeric substances was also preliminarily screened. A total of 24 luminescent isolates were obtained, with an abundance from C. agassizi specimens. All the isolates were taxonomically characterized and were related to different species of Photobacterium, with the exception of Vibrio sp. CLD11 that was from C. agassizi. The luxAB gene was detected in about the 90% of the analysed strains.

Neglected fishery data sources as indicators of pre‐industrial ecological properties of Mediterranean swordfish ( Xiphias gladius , Xiphiidae) - Brian R. MacKenzie; Piero Addis; Pietro Battaglia; Pierpaolo Consoli; Franco Andaloro; Gianluca Sarà; Anders Nielsen; Teresa Romeo (Fish and Fisheries, 2022)
Management of fish populations and ecosystems suffers from data and knowledge gaps, particularly with respect to how humans and nature affect dynamics at multi‐decadal and longer time scales. However, collection of new data which indicates population or ecosystem status is slow and expensive. Here we analyse c. 110 years of neglected fishery data for an overexploited top predator, swordfish, in the Mediterranean Sea. These data are available at scales of high time–space–biological resolution (i.e., sub‐weekly, sub‐regional sea; individual weights) and allow different ecological questions to be addressed than is possible with coarsely scaled data (e.g., annually resolved total catches aggregated over large sea areas). We constructed regional indicators of population status (relative abundance, mean individual size and its variability, migration phenology) covering most of the 20th century, and pre‐dating other population datasets by 50–70 years. The length and duration of these new time series allowed detection of significant multi‐annual/decadal variations in abundance and mean weight not detectable in shorter, more recent time series. These new data and evidence of multi‐annual variability in population variables improve knowledge of Mediterranean swordfish ecology. The findings provide a new basis on which further historical data recovery and analysis of contemporary data can provide new perspectives and opportunities for quantifying vulnerability of populations to exploitation and climate change.

Science and Dissemination for the UN Ocean Decade Outcomes: Current Trends and Future Perspectives - Francesco Caruso; Pietro Tedesco; Gerardo Della Sala; Fortunato Palma Esposito; Marco Signore; Simonepietro Canese; Teresa Romeo; Marco Borra; Claudia Gili; Donatella de Pascale (Frontiers in Marine Science, 2022)
The Ocean Decade (OD) is the name of a United Nations (UN) initiative devoted to ocean science for sustainable development. It started in 2021 and will provide an opportunity to create a new foundation, across the science-policy interface, to strengthen the sustainable management of oceans and coasts and, at same time, bring benefits for future generations. The OD will establish a common strategy to achieve the objectives of the 2030 Agenda for Sustainable Development and the other European Union (EU) and international agreements, such as the EU Marine Strategy Framework Directive (MSFD), the Marine Biodiversity Strategy and the UN World Assessment I and II aimed at preserving ocean health. Furthermore, the OD has several expected outcomes that concern different aspects of marine environment, including its enormous values for humans. Several entities will combine efforts to achieve these goals and science is at the forefront of the sustainable blue economy. Marine research is solving complex challenges through interdisciplinary approaches, revolutionizing our life and our interaction with the ocean. This review discusses recent advancements in science related to the OD outcomes. The role of new technology for ocean exploration and monitoring, the importance of omics science and biotechnology to deal with ocean pollution, and other innovative solutions are discussed. All of these are inspired by the idea of using marine resources in a sustainable way and without impacting in a negative way on marine ecosystems. The role of science communication is therefore considered a crucial issue to spread the OD messages and to reach the general public and stakeholders. Only by the integration of science, governance, industry and public, the OD will have any chance to succeed.

Age, Growth and Otolith Microstructure of the Spotted Lanternfish Myctophum punctatum Rafinesque 1810 - Francesco Longo; Danilo Malara; Maria Giulia Stipa; Pierpaolo Consoli; Teresa Romeo; Marilena Sanfilippo; Francesco Abbate; Franco Andaloro; Pietro Battaglia (Journal of Marine Science and Engineering, 2021)
This study investigated, for the first time, the age and growth of the spotted lanternfish Myctophum punctatum through an analysis of otolith microstructure. A total of 377 individuals were collected from the Strait of Messina (central Mediterranean Sea), ranging between 20.3 and 73.7 mm of standard length. Their length–weight relationship was estimated, and these outputs indicated an isometric growth, for all specimens and when males and females were analysed separately. The sagittal otoliths were removed from 185 fish, although the microincrement readings were considered valid for only 173 otoliths. Microincrement counts ranged from 32 to 48 (average = 37.6) in the otolith central zone, 30 to 56 (average = 44.3) in the middle zone, and 36 to 384 (average = 165.5) in the external zone. Overall, total microincrements ranged between 106 and 469. Different growth models (Gompertz, von Bertalanffy and logistic models) were considered, to understand which one fit best in describing the growth patterns in M. punctatum. The Gompertz model was then selected as the best-fitting model and its parameters for all individuals were L∞ = 74.79, k = 0.0084 and I = 139.60.

Correction to: Coating Lacticaseibacillus rhamnosus GG in Alginate Systems: an Emerging Strategy Towards Improved Viability in Orange Juice - Angela Bonaccorso; Nunziatina Russo; Alessia Romeo; Claudia Carbone; Maria Aurora Grimaudo; Carmen Alvarez-Lorenzo; Cinzia Randazzo; Teresa Musumeci; Cinzia Caggia (AAPS PharmSciTech, 2021)

Coating Lacticaseibacillus rhamnosus GG in Alginate Systems: an Emerging Strategy Towards Improved Viability in Orange Juice - Angela Bonaccorso; Nunziatina Russo; Alessia Romeo; Claudia Carbone; Maria Aurora Grimaudo; Carmen Alvarez-Lorenzo; Cinzia Randazzo; Teresa Musumeci; Cinzia Caggia (AAPS PharmSciTech, 2021)
Fruit juices are successfully proposed as suitable probiotic vehicles, but researchers’ efforts should be developed to avoid effects of bacteria overgrowing on sensory and nutritional cues of final products and to preserve viability of probiotic bacteria during storage. In the present study, encapsulation of Lacticaseibacillus rhamnosus GG strain in alginate systems was performed through ionotropic gelation technology. The alginate systems were optimized by using Box-Behnken Design to investigate the influence of three independent variables at three different levels: particle mean size and polydispersity index. The optimized probiotic-loaded alginate particles were added to orange juice samples. The viability of the probiotic strain, both as free and microencapsulated, was evaluated in orange juice stored at 5°C for 35 days. Morphology and size of probiotic-loaded alginate particles were found suitable for incorporation into juice. TEM analysis revealed that unloaded systems were clustered as nanoparticles (CL_NP), while the loaded sample appeared as a coated system (Coated_LGG). Microbiological evaluation revealed that the encapsulation assured the survival of Coated_LGG, with a reduction of less than 1-unit log in cellular density after 35 days of refrigerated storage in orange juice. Results indicated that the encapsulated bacteria did not affect the macroscopic properties neither the microbiological characteristic of orange juice; thus, it can be proposed as functional food.

Species and habitats of conservation interest in the Ecologically and Biologically Significant Area of the Strait of Sicily: a contribution towards the creation of a Specially Protected Areas of Mediterranean Importance - PIERPAOLO CONSOLI; CHIARA ALTOBELLI; PATRIZIA PERZIA; MARZIA BO; ANTONIETTA ROSSO; GIUSEPPINA ALONGI; DONATELLA SERIO; SIMONEPIETRO CANESE; TERESA ROMEO; FRANCO ANDALORO (Mediterranean Marine Science, 2021)
In 2015, the Strait of Sicily, which includes several banks, was candidate as a future Specially Protected Area of Mediterranean Importance (SPAMI) by the Contracting Parties of the Barcelona Convention. In this context, the present study aims to provide the first biological and ecological characterisation of this poorly known area, focusing on habitats and species of conservation concern. Surveys were carried through a remotely operated vehicle (ROV) and allowed the identification of 19 habitat types, mostly considered of priority interest by the SPA/BD Protocol of the Barcelona Convention. A total of 269 taxa were also identified, mostly Porifera, Cnidaria and Pisces, among which 115 species are of conservation concern according to the International Union for Conservation of Nature (IUCN) Red Lists, the Habitats Directive, the Bern Convention, the SPA/BD Protocol and CITES. ROV surveys allowed some interesting observations on poorly known species and habitats. Results underlined that remarkable discrepancies in species conservation status assessment that exist between the several lists of protected species considered. The IUCN Red Lists, although not legally binding for European States, are the most complete, but, in spite of this, the conservation policies in the EU are largely focused on the Habitats Directive, which is really not exhaustive. An exhaustive and legally binding instrument to protect species of conservation concern at European scale is highly recommended. Acquired results could be useful for the delimitation of a future SPAMI or a network of Marine Protected Areas (including the investigated banks) and the identification of zones within them suitable for different area-based management measures.

The last stage in the life history of the European conger eel Conger conger : a transformation before death - Pietro Battaglia; David Smith; Giovanni Ammendolia; Mauro Cavallaro; Teresa Maggio; Pierpaolo Consoli; Maria C. Guerrera; Franco Andaloro; Teresa Romeo (Journal of Fish Biology, 2020)
The taxonomic, morphological and meristic features of a dark eel caught by commercial trawling off the Gulf of Patti, southern Tyrrhenian Sea, Mediterranean Sea, February 17, 2017, showed it to be a female Conger conger . Histological analysis of gonads demonstrated that the individual was in a post‐spawning phase. X‐ray radiographs showed widespread decalcification of skeleton and teeth loss, confirming a strong mobilisation of somatic energy reserves needed for reproductive development.

Effects of microplastics on trophic parameters, abundance and metabolic activities of seawater and fish gut bacteria in mesocosm conditions - Gabriella Caruso; Cristina Pedà; Simone Cappello; Marcella Leonardi; Rosabruna La Ferla; Angelina Lo Giudice; Giulia Maricchiolo; Carmen Rizzo; Giovanna Maimone; Alessandro Ciro Rappazzo; Lucrezia Genovese; Teresa Romeo (Environmental Science and Pollution Research, 2018)

The impact of fisheries on vulnerable habitats: the case of trawling on circa-littoral grounds in the Strait of Sicily (central Mediterranean Sea) - Pierpaolo Consoli; Valentina Esposito; Manuela Falautano; Pietro Battaglia; Luca Castriota; Teresa Romeo; Mauro Sinopoli; Pietro Vivona; Franco Andaloro (Marine Biology Research, 2017)

Critical Inconsistencies in Early Implementations of the Marine Strategy Framework Directive and Common Fisheries Policy Objectives Hamper Policy Synergies in Fostering the Sustainable Exploitation of Mediterranean Fisheries Resources - Saša Raicevich; Pietro Battaglia; Tomaso Fortibuoni; Teresa Romeo; Otello Giovanardi; Franco Andaloro (Frontiers in Marine Science, 2017)

Influence of lunar phases, winds and seasonality on the stranding of mesopelagic fish in the Strait of Messina (Central Mediterranean Sea) - Pietro Battaglia; Giovanni Ammendolia; Mauro Cavallaro; Pierpaolo Consoli; Valentina Esposito; Danilo Malara; Ignazio Rao; Teresa Romeo; Franco Andaloro (Marine Ecology, 2017)
The shore stranding of mesopelagic fauna is a recurrent phenomenon in the Strait of Messina (Central Mediterranean Sea). The aim of this paper is to test the influence of lunar phases, winds and seasons upon the frequency of occurrence of strandings of mesopelagic fish. Species abundance in relation to these factors was quantified for the first time. Specimens were collected stranded on the shore along the Sicilian coast of the Strait of Messina between 2008 and 2016. Overall 32 species belonging to seven families (Gonostomatidae, Microstomatidae, Myctophidae, Paralepididae, Phosichthyidae, Sternoptychidae, Stomiidae) were found stranded. Myctophidae was the family including the highest number of species (16), whereas Gonostomatidae was the most abundant in terms of total number of individuals (47.2%), mainly thanks to the species Cyclothone braueri . The moon, which influences the strength of currents (highest during full and new moon phases) and irradiance (higher in some lunar phases, such as the full moon), affected the abundance of stranded mesopelagic fish in the study area. The highest number of stranding events was recorded during the new moon: 34.6% of the total relative abundance of stranded mesopelagic fish. Wind blowing from the sea towards the coastline (southeasterly and easterly winds) created the best conditions for strandings. The highest abundance of stranded specimens was recorded during the winter season.

Assessing the relationship between cetacean strandings (Tursiops truncatus and Stenella coeruleoalba) and fishery pressure indicators in Sicily (Mediterranean Sea) within the framework of the EU Habitats Directive - Roberto Crosti; Antonella Arcangeli; Teresa Romeo; Franco Andaloro (European Journal of Wildlife Research, 2017)

Plastic Debris Occurrence, Convergence Areas and Fin Whales Feeding Ground in the Mediterranean Marine Protected Area Pelagos Sanctuary: A Modeling Approach - Maria Cristina Fossi; Teresa Romeo; Matteo Baini; Cristina Panti; Letizia Marsili; Tommaso Campani; Simonepietro Canese; François Galgani; Jean-Noël Druon; Sabina Airoldi; Stefano Taddei; Maria Fattorini; et al. (Frontiers in Marine Science, 2017)

Suburban ecology of the crested porcupine in a heavily poached area: a global approach - Sandro Lovari; Maria Teresa Corsini; Barbara Guazzini; Giorgia Romeo; Emiliano Mori (European Journal of Wildlife Research, 2017)

Erratum to: The deep-water squid Octopoteuthis sicula Rüppell, 1844(Cephalopoda: Octopoteuthidae) as the single species of the genus occurring in the Mediterranean Sea - Patrizia Jereb; Rita Cannas; Porzia Maiorano; Giambattista Bello; Fulvio Garibaldi; Marco Mereu; Francesco G. Ancona; Giovanni Ammendolia; Pietro Battaglia; Önder Duysak; Hendrik Jan T. Hoving; Eugenia Lefkaditou; et al. (Marine Biology, 2016)

Assessing persistent organic pollutants (POPs) in the Sicily Island atmosphere, Mediterranean, using PUF disk passive air samplers - Karla Pozo; Margherita Palmeri; Valeria Palmeri; Victor H. Estellano; Marie D. Mulder; Christos I. Efstathiou; Gian Luca Sará; Teresa Romeo; Gerhard Lammel; Silvano Focardi (Environmental Science and Pollution Research, 2016)

The deep-water squid Octopoteuthis sicula Rüppell, 1844 (Cephalopoda: Octopoteuthidae) as the single species of the genus occurring in the Mediterranean Sea - Patrizia Jereb; Rita Cannas; Porzia Maiorano; Giambattista Bello; Fulvio Garibaldi; Marco Mereu; Francesco G. Ancona; Giovanni Ammendolia; Pietro Battaglia; Önder Duysak; Hendrik Jan T. Hoving; Eugenia Lefkaditou; et al. (Marine Biology, 2016)

Pseudonereis anomala (Polychaeta, Nereididae) expands its range westward: first Italian record in Augusta and Siracusa harbours - Michela D’Alessandro; Luca Castriota; Pierpaolo Consoli; Teresa Romeo; Franco Andaloro (Marine Biodiversity, 2016)

Environmental quality assessment of Grand Harbour (Valletta, Maltese Islands): a case study of a busy harbour in the Central Mediterranean Sea - Teresa Romeo; Michela D’Alessandro; Valentina Esposito; Gianfranco Scotti; Daniela Berto; Malgorzata Formalewicz; Seta Noventa; Silvia Giuliani; Simona Macchia; Davide Sartori; Angelo Mazzola; Franco Andaloro; et al. (Environmental Monitoring and Assessment, 2015)

Distribution and ecology of the tube-dweller Ampelisca ledoyeri (Amphipoda: Ampeliscidae) associated with the hydrothermal field off Panarea Island (Tyrrhenian Sea, Mediterranean) - Valentina Esposito; Salvatore Giacobbe; Andrea Cosentino; Caterina Stefania Minerva; Teresa Romeo; Simonepietro Canese; Franco Andaloro (Marine Biodiversity, 2015)

Cephalopod prey in the stomach contents of odontocete cetaceans stranded in the western Mediterranean Sea - Cristina Pedà; Pietro Battaglia; Alessia Scuderi; Alessandro Voliani; Cecilia Mancusi; Franco Andaloro; Teresa Romeo (Marine Biology Research, 2015)

Feeding habits of juvenile fishes belonging to three medusivorous species (Centrolophidae and Nomeidae) from the Strait of Messina (central Mediterranean Sea) - Pietro Battaglia; Simona Musolino; Valentina Esposito; Giovanni Ammendolia; Pierpaolo Consoli; Franco Andaloro; Teresa Romeo (Marine Biology Research, 2014)

Diet and prey selectivity of the red mullet, Mullus barbatus (Pisces: Mullidae), from the southern Tyrrhenian Sea: the role of the surf zone as a feeding ground - Valentina Esposito; Franco Andaloro; Daniela Bianca; Antonino Natalotto; Teresa Romeo; Gianfranco Scotti; Luca Castriota (Marine Biology Research, 2014)

Alteration of potential harmful elements levels in sediments and biota from the central Mediterranean Sea (Aeolian Archipelago) following an episode of intense volcanic activity - Franco Andaloro; Teresa Romeo; Monia Renzi; Cristiana Guerranti; Guido Perra; Pierpaolo Consoli; Patrizia Perzia; Silvano Ettore Focardi (Environmental Monitoring and Assessment, 2012)

Relationship between swordfish swimming behaviour and sea surface temperature in the central Mediterranean Sea during the reproductive period - Teresa Romeo; Patrizia Perzia; Valentina Esposito; Danilo Malara; Pietro Battaglia; Pierpaolo Consoli; Simone Canese; Franco Andaloro (Marine Biology Research, 2011)

Feeding habits and selectivity of the wide-eyed flounder, Bothus podas (Delaroche, 1809) (Bothidae) from the southern Tyrrhenian sea - Valentina Esposito; Luca Castriota; Pierpaolo Consoli; Teresa Romeo; Manuela Falautano; Franco Andaloro (Marine Biology Research, 2010)

Biomarkers of Exposure and Effects for Assessing Toxicological Risk of Endocrine Disrupters in Top Predators of the Mediterranean Sea - M. Cristina Fossi; Silvia Casini; Letizia Marsili; Stefania Ancora; Gabriele Mori; Giovanni Neri; Antonella Ausili; Teresa Romeo; Alessandra Moscatelli; Giuseppe Notarbartolo Di Sciara (Marine Ecology, 2002)
Endocrine Disrupting Chemicals (EDCs) have the potential to alter hormone pathways that regulate reproductive processes in wildlife and fisheries. In this research the unexplored hypothesis that Mediterranean top predator species (such as large pelagic fish and marine mammals) are potentially at risk due to EDCs is investigated. In the Mediterranean environment, top predators accumulate high concentrations of polyhalogenated aromatic hydrocarbons (PHAHs) and toxic metals, incurring high toxicological risk. Here we illustrate the need to develop sensitive biomarkers for evaluation of toxicological risk in top marine predators (Xiphias gladius, Thunnus thynnus thynnus) and non‐lethal techniques, such as non‐destructive biomarkers, for the hazard assessment of threatened species exposed to EDCs, such as marine mammals ( Stenella coeruleoalba, Tursiops truncatus, Delphinus delphis and Balaenoptera physalus ).